Electron backscatter diffraction analysis and orientation mapping of monazite - Reddy, Steven; Clark, Chris; Timms, Nicholas Eric; Eglington, B. (The Mineralogical Society, 2010)
Electron backscatter diffraction (EBSD) analysis of monazite requires a comparison of empirically collected electron backscatter patterns (EBSPs) with theoretical diffraction data, or 'match units', derived from known crystallographic parameters. Published crystallographic data derived from compositionally varying natural and synthetic monazite are used to calculate ten different match units for monazite. These match units are used to systematically index EBSPs obtained from four natural monazite samples with different compositions. Analyses of EBSD data, derived from the indexing of five and six diffraction bands using each of the ten match units for 10,000 EBSPs from each of the four samples, indicate a large variation in the ability of the different match units to correctly index the different natural samples. However, the use of match units derived from either synthetic Gd or Eu monazite crystallographic data yield good results for three of the four analysed monazites. Comparison of sample composition with published monazite compositions indicates that these match units are likely to yield good results for the EBSD analysis of metamorphic monazite. The results provide a clear strategy for optimizing the acquisition and analysis of EBSD data from monazite but also indicate the need for the collection of new crystallographic structure data and the subsequent generation of more appropriate match units for natural monazite.